Nutrients Content in Some Vegetables Grown in South-Central Coastal Regions of Bangladesh (The Agriculturists, 2018)
Soil salinity is one of the most important abiotic stresses for crop production. A study was conducted to analyze the relationship between salinity level and nutrient contents in some popular vegetables grown in some selected tidal areas of Barguna and Patuakhali districts of Bangladesh. Samples of six different vegetables such as bottle gourd leaf (Lagenaria siceraria), sweet gourd leaf (Cucurbita maxima), radish leaf (Raphanus sativus), bean (Lablab niger), red amaranth (Amaranthus gangeticus) and spinach (Spinacia oleracea) were collected along with soils from different locations of the study areas and were analyzed for phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulphur (S) contents. Soil pH and electrical conductivity (EC) were determined. In saline areas, comparatively lower amounts of P, K, Ca, Mg and S were detected in most of the collected vegetables than those of non-saline areas. Conversely, bottle gourd leaf, radish leaf and bean accumulated comparatively higher amount of Ca at higher salinity levels. The uptake of P by bottle gourd leaf and radish leaf, Mg by bottle gourd leaf and red amaranth was also higher in the saline soil. The inconsistent uptake of Ca, Mg and P were found in some vegetables due to the differences of fertilizer application and intercultural operation. The vegetables could tolerate moderate soil salinity (soil EC up to7.9 dSm-1) and might be recommended to grow in the tidal saline areas of Barguna and Patuakhali districts of Bangladesh.The Agriculturists 2018; 16(2) 43-57